Chinese herbal bath therapy for the treatment of uremic pruritus: meta-analysis of randomized controlled trials - Wenxuan Xue; Yanhua Zhao; Mengyun Yuan; Zhiqiang Zhao (BMC, 2019)
Abstract Background Chinese herbal bath therapy (CHBT) is a traditional external therapy that has been used for the treatment of uremic pruritus (UP) in China. We conducted a meta-analysis to evaluate the efficacy and safety of CHBT for UP. Methods We searched seven databases for studies published since database inception to September 1, 2018. Randomized trials evaluating CHBT for UP were collected. The therapeutic effects of CHBT were measured by the pruritus level (via the visual analogue scale (VAS) or the symptom score scale) and the total effective rate. We combined studies using mean difference (MD) for continuous outcomes and using risk ratio for dichotomous data, both with 95% confidence intervals. RevMan V.5.3 software was used to assess the data reported and perform the meta-analysis. Results Seventeen articles including 970 patients were identified. All participants were haemodialysis (HD) patients. CHBT is administered by immersing the whole body in a prepared herbal water bath. On average, an herbal bath prescription included 11 Chinese herbs. The mean treatment duration was 4.7 weeks. Compared with basic treatment (HD or haemoperfusion (HP)) and adding a control of sham CHBT, clear hot water bath, or calamine lotion, CHBT plus basic treatment reduced the VAS score (MD = − 2.38; 95% confidence intervals [CI], − 3.02 to − 1.74; P < 0.00001) and the symptom score (MD = − 8.42; 95% confidence intervals [CI], − 12.47 to − 4.36; P < 0.00001) and had a higher total effectiveness rate (risk ratio [RR] = 1.46; 95% CI, 1.31 to 1.63; P < 0.00001). Conclusions In conclusion, CHBT could be a complementary therapy for improving pruritic symptoms in uraemia patients. More rigorously designed, multicentre, prospective RCTs are warranted to further identify the efficacy and safety of CHBT. Trial registration Systematic review registration: [PROSPERO registration: CRD42018108506].